Ettringite synchrotron energy dispersive diffraction study - Muhamad, M. N.; Barnes, P.; Fentiman, C. H.; Hausermann, D.; Pollman, H.; Rashid, S. (Faculty of Science, University Teknologi Malaysia, 2006)

(untitled)
Synchrotron radiation - energy dispersive diffraction has been used as a method for in-situ studies on the hydration of cements. The rapid data capture of the technique permits a time-resolved analysis of hydrating cement species under realistic (chosen) conditions. In this paper, we report on a study of the early hydration of minepack mixtures forming ettringite: the growth can be perceived over steps as small as 20 seconds, also the shifts in diffraction peak positions which are interpreted in terms of a time-dependent composition of the ettringite phase